Assessment of Bacterial Sealing Ability of Two Different Bio-Ceramic Sealers in Single-Rooted Teeth Using Single Cone Obturation Technique: An In Vitro Study - Doaa M. AlEraky; Ahmed M. Rahoma; Hatem M. Abuohashish; Abdullh AlQasser; Abbas AlHamali; Hussain M. AlHussain; Hussain M. AlShoalah; Zakrya AlSaghah; Abdulrahman Khattar; Shimaa Rifaat (Applied Sciences, 2023)
The long-term success of root canal treatment requires the prevention of bacterial leakage between canal walls and root canal obturation. In this study, we compared the leakage of Enterococcus faecalis in thirty single-rooted mandibular premolars divided into three groups. The roots in two experimental groups were obturated using a single-cone obturation technique with two different bio-ceramic sealers (MTA Fillapex and CeraSeal) while the roots in the conventional group were obturated using the lateral condensation technique with an epoxy resin sealer (AH Plus). A bacterial leakage test was carried out using a modified microbial leakage model. In the MTA Fillapex group, 30% of the specimens showed a positive sign for bacterial leakage, while 80% of samples in the CeraSeal group leaked. In the AH Plus group, 50% of specimens had bacterial leakage in the canals. The variation of the average number of days between the groups was not found to be significantly different. Taken together, bio-ceramic sealers with single-cone obturation demonstrated comparable results to the resin-based sealer with lateral condensation technique in terms of sealing efficiency against Enterococcus faecalis. Additionally, MTA Fillapex could provide a better sealing ability than CeraSeal bio-ceramic sealer.